Diagnosis of rejection following heart transplantation: diving into the future - Rao, Shaline; Ali, Syed Zain; Singh, Arushi; Rana, Mittal; Moussa, Mohamed; Ahmed, Kinza; Golob, Stephanie; Cusumano, Lauren; Harrington, Alana; Wang, Andrew; Chandrasekhar, Sanjay; Alam, Amit (Frontiers in Transplantation, 2026)
Since the standardization of the grading system for pathologic diagnosis of antibody-mediated and acute cellular rejection, endomyocardial biopsy has remained the gold-standard. However, biopsies are invasive, costly, and limited by sampling error. As such, adjuvant non-invasive methods including cardiac biomarkers, imaging including cardiac magnetic resonance and echocardiography, and donor-specific antibodies and non-HLA antibodies have been traditionally used. However, all these techniques are limited by either sensitivity or specificity. More recently, there has been a shift to other contemporary non-biopsy surrogate markers for rejection surveillance including donor-derived cell free DNA, gene expression profiling, and messenger RNA and micro-RNA in tissue. Herein we review the methods currently utilized to diagnose rejection and their limitations. We find that while there have been significant advancements in technology and non-invasive techniques, no current method alone adequately diagnoses rejection (Central Image). Thus, future studies are warranted to investigate new strategies involving a multi-modal approach that incorporates non-invasive diagnostic methods and personalized medicine to monitor postoperative progression in heart transplant patients.